Probiotics in medical sciences education: a survey-based study in Oman. - AbuKhader, Majed; Ashouri, Yasmin; Yasir Al-Ani, Sarah; Al-Harthy, Nutayla; Aljebouri, Amnah (International Journal of Health Promotion & Education, 2024)
Medical sciences students are the future healthcare providers and must be equipped with relevant basic and latest developments in probiotics during their education to understand its applications in clinical practice. The aim of this study was to evaluate the knowledge and attitudes of medical sciences students; medicine and dental students, studying in Oman. This is a cross sectional survey-based study which was conducted in three Omani higher education institutions. The questionnaire was composed of 20 close-ended questions grouped into demographic and students' knowledge and attitudes towards probiotics. Among the 357 students there were 197 medicine (MD) students and 160 dental (BDS) students. Results showed that both MD (89.3%) and BDS (95%) students believe that they don't have enough knowledge about probiotics which was statistically significant (p < 0.028). Students from both groups showed uncertainty in some aspects related to probiotics when answering some questions in the survey. Responses obtained from the preclinical and clinical MD and BDS students showed variations which were statistically significant (p < 0.05). Both preclinical and clinical MD students showed positive attitudes towards the use of probiotics in practice while clinical BDS students have more reserved attitudes towards it than preclinical BDS. The MD and BDS students' poor knowledge and the reserved attitude of BDS students towards probiotics were the main conclusions in this study. This should be addressed by redesigning relevant courses in medical sciences programs' curriculum to provide relevant information about probiotics to medical sciences students considering preclinical and clinical stages of their medical education.